Genomics, genetics and breeding of common bean in Africa: A review of tropical legume project. (17th April 2018) - Mukankusi, Clare; Raatz, Bodo; Nkalubo, Stanley; Berhanu, Fenta; Binagwa, Papias; Kilango, Michael; Williams, Magdalena; Enid, Katungi; Chirwa, Rowland; Beebe, Steve
Abstract: Common bean ( Phaseolus vulgaris L.) is an important legume crop worldwide. The International Centre for Tropical Agriculture (CIAT) and its national partners in Africa aim to overcome production constraints of common bean and address the food, nutrition needs and market demands through development of multitrait bean varieties. Breeding is guided by principles of market‐driven approaches to develop client‐demanded varieties. Germplasm accessions from especially two sister species, P. coccineus and P. acutifolius, have been utilized as sources of resistance to major production constraints and interspecific lines deployed. Elucidation of plant mechanisms governing pest and disease resistance, abiotic stress tolerance and grain nutritional quality guides the selection methods used by the breeders. Molecular markers are used to select for resistance to key diseases and insect pests. Efforts have been made to utilize modern genomic tools to increase scale, efficiency, accuracy and speed of breeding. Through gender‐responsive participatory variety selection, market‐demanded varieties have been released in several African countries. These new bean varieties are a key component of sustainable food systems in the tropics.